The Paradox of Judicial Power: The Indonesian Constitutional Court’s Activism in the Post‑Ahok Era and Its Impact on Electoral Democracy - Christopher Panal Lumban Gaol; Samuel Frans Boris Situmorang; Seno Wibowo Gumbira; Irsyad Sudirman; Suryani Intan Pratiwi Puwa (Inovasi Pratama Internasional. Ltd, 2026)
This study investigates the paradoxical role of the Indonesian Constitutional Court (Mahkamah Konstitusi, MK) in shaping electoral democracy after the 2017 Jakarta gubernatorial election that convicted Basuki Tjahaja Purnama (Ahok) for blasphemy. While judicial activism is generally seen as a mechanism to defend constitutional rights, the post‑Ahok period witnessed a surge in MK rulings that override electoral commissions and construct new legal norms, often with majoritarian and exclusionary undertones. Employing a panel fixed‑effects regression on 34 Indonesian provinces from 2014 to 2023, this research quantitatively examines the relationship between MK activism in electoral disputes and provincial electoral democracy scores. The independent variable, a novel Judicial Activism Index (JAI), captures annual counts of MK decisions that annulled KPU determinations or introduced expansive interpretations in pemilu and pilkada cases. The results reveal a significant negative interaction effect between the JAI and the Post‑Ahok dummy (2017–2023) on the Provincial Electoral Democracy Score. In the post‑Ahok period, a one‑unit increase in activist rulings is associated with a 1.8‑point decline in democratic quality, controlling for economic and political covariates. The findings unveil a paradox: a court empowered to guard democracy can, under conditions of heightened identity politics, become a vehicle for democratic regression. The study calls for recalibrating the MK’s self‑restraint doctrine to prevent judicial overreach from undermining electoral pluralism